The Effect of Propolis (Bee Glue) on Sepsis: A Systematic Review - Stephanie Jesslyn; Ririe Fachrina Malisie (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2025)
Background: With pathogenic resistance and risk of dysbiosis, antimicrobial therapy for sepsis becomes less effective. Therefore, there is a need for an additional therapy, such as immunomodulation, either directly or through modulation of the gut microbiota. Propolis, or bee glue, has immunomodulatory properties and positive effects on the gut microbiota. This systematic review aims to assess the potential of propolis as an adjunctive therapy in alleviating sepsis through pathways associated with gut microbiota, such as inflammation and oxidative stress. Methods: This study was made in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The keywords for the literature search and study relevance were determined with the Population, Intervention, Comparison, and Outcome (PICO) formula: Population (P): Septic human or animal; Intervention (I): Propolis administration; Comparison (C): Septic human or animal without propolis administration; Outcome (O): Gut microbiota and inflammatory as well as oxidative stress biomarkers. A literature search was conducted in PubMed, ScienceDirect, and Google Scholar to obtain relevant studies with a download period from January 2015 to March 2025. Results: The literature search yielded 3,189 articles, with four articles eligible for inclusion in this literature review. The four studies were animal studies and reported that propolis administration improved sepsis by reducing inflammatory and oxidative stress biomarkers and mitigating organ damage. None of the studies reported the outcome on gut microbiota in sepsis. Conclusion: Propolis showed potential as an adjunctive therapy for sepsis through its anti-inflammatory and antioxidative effects, but there is no evidence from human studies.